Freedom and giving in game streams: A Foucauldian exploration of tips and donations on Twitch. Issue 6 (23rd March 2021) - Yoganathan, Vignesh; Osburg, Victoria‐Sophie; Stevens, Callum James
Abstract: Twitch is a full‐fledged marketplace for game consumption, where gameplay is live streamed by players for the benefit of viewers/followers. Using Foucault's notions of freedom as a practice, we provide a psychosocial understanding of game stream engagement, and especially, user motivations for tipping streamers or donating to charity (i.e., "giving"). Following a netnographic approach, we analyse contributions to a large online forum and data gathered from 15 focus groups. We find that giving arises as an outcome of users exercising their freedom, whilst negotiating personal difficulties, for social gratification (e.g., status among peers), self‐determination (i.e., feeling control over one's life), and self‐extension (i.e., feeling affinity with others to achieve ideal self). By providing opportunities for self‐extension and self‐determination, which lead to better connectivity and stronger community support compared to social media, Twitch enables users to "give freely" (i.e., without obligation or compunction). Consequently, Twitch offers scope for more effective and mutually beneficial means of fundraising than traditional nonprofit marketing strategies, particularly by reaching younger target groups. Ultimately, the paper integrates three widely used theories under one (Foucauldian) metatheoretical perspective and highlights the central role of freedom in understanding game stream user engagement. Practical implications for nonprofit fundraising are also considered.